2018
DOI: 10.3390/biom8030079
|View full text |Cite
|
Sign up to set email alerts
|

Role of the HPRG Component of Striated Muscle AMP Deaminase in the Stability and Cellular Behaviour of the Enzyme

Abstract: Multiple muscle-specific isoforms of the Zn2+ metalloenzyme AMP deaminase (AMPD) have been identified based on their biochemical and genetic differences. Our previous observations suggested that the metal binding protein histidine-proline-rich glycoprotein (HPRG) participates in the assembly and maintenance of skeletal muscle AMP deaminase (AMPD1) by acting as a zinc chaperone. The evidence of a role of millimolar-strength phosphate in stabilizing the AMPD-HPRG complex of both AMPD1 and cardiac AMP deaminase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 113 publications
0
4
0
Order By: Relevance
“…In this regard, some studies indicate that the expression of AMPD1 and AMPD3 genes may be coordinated in myocytes to effect production of an AMPD holoenzyme. 77 , 78 Therefore, both isoforms may be required for proper AMPD activity. In this regard, Miller et al.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, some studies indicate that the expression of AMPD1 and AMPD3 genes may be coordinated in myocytes to effect production of an AMPD holoenzyme. 77 , 78 Therefore, both isoforms may be required for proper AMPD activity. In this regard, Miller et al.…”
Section: Discussionmentioning
confidence: 99%
“…These isoforms are located on striated muscle filaments and participate in the inhibition of the calcium-induced myosin ATPase activity, which is closely associated with meat quality [86]. The AMPD1, small muscle protein X-linked, and triadin (TRDN) genes are closely related to the improvement of meat quality [87][88][89]. In the present study, TTN, LDB3, FLNC, TRDN, AMPD1, MBNL1, MYBPC1, and LOC100349824 were the key nodes in the network and probably influence the formation of skeletal muscle fiber types in obese rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…We reported that the catalytic subunit of rabbit white muscle AMPD1 contains a structurally bridged dinuclear metallocenter [15] composed by the catalytic zinc bound to the C-terminus of the enzyme (corresponding to the single zinc bound at the catalytic site described for murine adenosine deaminase [99] and yeast AMPD [100]) and a zinc bound to the putative zinc-binding site in the N-terminal region. The rabbit histidine-proline-rich-glycoprotein (HPRG) has been reported to be associated with the catalytic subunit of rabbit white skeletal muscle AMPD1 [101] to form a 1:1 molecular adduct (two 85 kDa catalytic subunits assembled with two 73 kDa HPRG subunits) [102][103][104]. When the HPRG component was separated by zinc-affinity chromatography the solubility of the catalytic subunit of the enzyme was markedly reduced [105] strengthening the hypothesis that HPRG functions as a zinc metallochaperone in the formation of the AMPD1 heterotetramer.…”
Section: Functional Characteristics Of Ampd Isoforms In Muscle Fibers...mentioning
confidence: 99%
“…In a recent review we have extensively described the data that support the hypothesis that HPRG might act as a zinc chaperone for AMPD1 [ 104 ]. In addition to the data of colocalization of AMPD1 and HPRG discussed above, HPRG is consistently purified as a complex with rabbit skeletal muscle AMPD1 and the isolation by zinc-affinity chromatography of the HPRG component resulted in the precipitation of the AMPD1 catalytic subunits [ 105 ].…”
Section: Introductionmentioning
confidence: 99%